National and sub-national pediatric cancer mortality in Iran, 2000–2015 - Rezaei, N; Pishgar, F; Yoosefi, M; Sheidaei, A; Saeedi Moghaddam, S; Mansouri, A; Tahernia, L; Naderimagham, S; Modirian, M; Pazhuheian, F; Rezaei, N; Namazi Shabestari, A; et al. (Academy of Medical Sciences of I.R. Iran, 2019)
Background: Cancer, a common disease in adulthood, is a rare albeit slowly increasing condition among children. Currently, limited data are available on the incidence, prevalence, and mortality of these diseases in many regions, including developing countries. Herein, we are reporting national and sub-national estimates on deaths due to childhood cancers between 2000 and 2015 in Iran.